Flexibility in faithfulness of Dark-bellied Brent Geese Branta b. bernicla to moulting sites - Ebbinge, Bart S.; Prokosch, Peter; Spaans, Bernard; MÃ¼skens, Gerhard J.D.M.; Bom, Roeland; Kokorev, Yakov I.; Syroechkovskiy, Evgeny E. (Wildfowl, 2013)
The distribution of Dark-bellied Brent Geese Branta b. bernicla moulting on theÂ Taimyr Peninsula, in the Russian arctic, varies between years depending on whetherÂ the birds had a successful breeding season. Counts made of moulting flocks showÂ that major shifts in numbers occur, particularly in non-breeding years, when inÂ line with Salomonsenâ€™s (1968) hypothesis a higher proportion of the populationÂ moults further north. For instance, the delta of the Lower Taimyr River in theÂ northern part of the Taimyr Peninsula held 10-times more moulting Dark-belliedÂ Brent Geese in 1989, a non-breeding year, than it did in the good 1990 breedingÂ season. At a more local scale, in good breeding years family groups with smallÂ goslings tend to move away from breeding islands in the Pyasina Delta, westernÂ Taimyr, to avoid gosling predation by Taimyr Gulls Larus taimyrensis which nest inÂ colonies on the same islands, whereas in poor breeding years adult geese concentrateÂ on these same islands to moult and avoid the mainland sites used for moulting inÂ good breeding years. Failed breeders have greater freedom than parent birds toÂ choose where to moult as successful breeders remain with their goslings to protectÂ and guide them to the safest nursery and moult areas. Re-captures of ringed DarkbelliedÂ Brent Geese at a moulting site in the Pyasina Delta found that, in poorÂ breeding years, up to one-fifth the birds had moulted at the site previously, but that theÂ majority of ringed birds known to be still alive were not site-faithful to theirÂ moulting grounds.